Sex differences in morphine sensitivity of neuroligin-3 knockout mice. - Brandner, Dieter D.; Mashal, Mohammed A.; Grissom, Nicola M.; Rothwell, Patrick E. (Psychopharmacology, 2024)
Sex has a strong influence on the prevalence and course of brain conditions, including autism spectrum disorders. The mechanistic basis for these sex differences remains poorly understood, due in part to historical bias in biomedical research favoring analysis of male subjects, and the exclusion of female subjects. For example, studies of male mice carrying autism-associated mutations in neuroligin-3 are over-represented in the literature, including our own prior work showing diminished responses to chronic morphine exposure in male neuroligin-3 knockout mice. We therefore studied how constitutive and conditional genetic knockout of neuroligin-3 affects morphine sensitivity of female mice, using locomotor activity as a proxy for differences in opioid sensitivity that may be related to the pathophysiology and treatment of autism spectrum disorders. In contrast to male mice, female neuroligin-3 knockout mice showed normal psychomotor sensitization after chronic morphine exposure. However, in the absence of neuroligin-3 expression, both female and male mice show a similar change in the topography of locomotor stimulation produced by morphine. Conditional genetic deletion of neuroligin-3 from dopamine neurons increased the locomotor response of female mice to high doses of morphine, contrasting with the decrease in psychomotor sensitization caused by the same manipulation in male mice. Together, our data reveal that knockout of neuroligin-3 has both common and distinct effects on morphine sensitivity in female and male mice. These results also support the notion that female sex can confer resilience against the impact of autism-associated gene variants.